POVERTY REDUCTION IN INDONESIA: A CHALLENGE FACING ASEAN ECONOMIC COMMUNITY - Kindangen, Paulus; Paruntu, Carolus Paulus (Journal of Asean Studies on Maritime Issues, 2015)
Poverty reduction is an important agenda of Indonesian government. Endeavors to reduce poverty require identification of its main influencing factors. This research was conducted to showÂ the role of economic growth and entrepreneurship in alleviating poverty in Indonesia. Descriptive analysis was done using secondary data and several empirical findings. This study shows that poverty in Indonesia decreased as the economy grew continuously in the long period of time. During the Asia financial crisis poverty jumped up, but then reduced again as the crisis ended and the economic growth did persist. This conclusion is in line with findings of various empirical studies. Two empirical studies in North Sulawesi indicate that entrepreneurship influence household income positively. These findings state that entrepreneurship or entrepreneurship spirit enable households to perform well in economic activities result in higher household income. As houshold income increases, poverty reduces. It means that entrepreneurship has positive influence on poverty reduction. In macroeconomic view, increased income ofÂ households causes increased economic growth. This study concludes that economic growth reduces poverty and that entrepreneurship has positive influence on economic growth as well as poverty reduction. It is recommended that, the endeavor to reduce poverty should always be one of the government priorities and that the government should keep on struggling to foster economic growth as an important way to reduce poverty. Poverty reduction as a result of economic growth supported by strong entrepreneurship enables this country to be better prepared facing Asean Economic Community.